2016
DOI: 10.3389/fnhum.2016.00413
|View full text |Cite
|
Sign up to set email alerts
|

Rod Driven Frequency Entrainment and Resonance Phenomena

Abstract: A controversy exists on photic driving in the human visual cortex evoked by intermittent photic stimulation. Frequency entrainment and resonance phenomena are reported for frequencies higher than 12 Hz in some studies while missing in others. We hypothesized that this might be due to different experimental conditions, since both high and low intensity light stimulation were used. However, most studies do not report radiometric measurements, which makes it impossible to categorize the stimulation according to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
10
23
0
Order By: Relevance
“…For the analysis, the EEG signal was divided into three stages: baseline pre-stimulus (the 1,000-ms period just preceding the stimulus onset), SSVEP interval (4 s of the response, starting 500 ms after stimulus onset), and post-stimulus stage (from the stimulus offset until the time at which the oscillation returned to baseline; Figure 2C). The selection of the SSVEP interval was based on previous works indicating that a robust, stable entrainment is achieved after 400 ms of stimulation (Wacker et al, 2011;Halbleib et al, 2012;Salchow et al, 2016).…”
Section: Entrainment Experimentsmentioning
confidence: 99%
“…For the analysis, the EEG signal was divided into three stages: baseline pre-stimulus (the 1,000-ms period just preceding the stimulus onset), SSVEP interval (4 s of the response, starting 500 ms after stimulus onset), and post-stimulus stage (from the stimulus offset until the time at which the oscillation returned to baseline; Figure 2C). The selection of the SSVEP interval was based on previous works indicating that a robust, stable entrainment is achieved after 400 ms of stimulation (Wacker et al, 2011;Halbleib et al, 2012;Salchow et al, 2016).…”
Section: Entrainment Experimentsmentioning
confidence: 99%
“…The extraction of steady-state evoked potentials from the measured EEG essentially relies on averaging subsequently acquired EEG epochs time-locked to the stimulus . Furthermore, the classical time-domain averaging of EEG epochs has been extremely useful for analyzing physiological processes such as the generation and extinction of SSVEP 17,18 . Presenting consecutive trains of flicker lights and averaging subsequent epochs within a recording, Wacker et al 19 observed that the phase-locking index of the SSVEP rapidly increased during the first 400 ms of stimulation and remained high afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Those behaviors have been interpreted as the engaging/disengaging effect of the observed oscillations, which is a consequence of the nonlinear information processing in the human visual system 17 . Alternatively, it is known that under certain experimental conditions, the flicker stimulation can elicit on-responses at the beginning, and off-responses at the end of stimulation trains instead of neural entrainment 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the first investigation of frequency entrainment using simultaneously recorded EEG and EMG signals during the IPS with frequency, which was adopted to the individual alpha rhythm was performed. Furthermore, in [14] a rod-driven PD effect was analysed and it was shown that strong alpha resonance phenomena exist for rodinput at stimulation frequencies around the individual alpha rhythm (0.95fα − 1.10fα) and the first subharmonic (0.50fα − 0.55fα). In [14] was shown that the rod-driven PD effect is limited by the flicker fusion threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in [14] a rod-driven PD effect was analysed and it was shown that strong alpha resonance phenomena exist for rodinput at stimulation frequencies around the individual alpha rhythm (0.95fα − 1.10fα) and the first subharmonic (0.50fα − 0.55fα). In [14] was shown that the rod-driven PD effect is limited by the flicker fusion threshold.…”
Section: Introductionmentioning
confidence: 99%